2010
DOI: 10.4049/jimmunol.1002518
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Induction of NK Activation by 2B4 (CD244) via Its Cognate Ligand

Abstract: We have previously shown that coincubation of purified B cells with IL-2–propagated NK cells can result in the induction of IL-13 mRNA and that the induction requires the presence of CD48 on B cells and 2B4 on NK cells. Because both of these molecules are expressed on NK cells, it is surprising that very little IL-13 mRNA can be detected in the absence of B cells. We have now found that incubation of NK cells on plates containing immobilized anti-CD48 Abs results in the clustering of CD48 and colocalization wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Surprisingly, however, anti-CD48 immobilized on plastic, can stimulate NK cells to augment their production of cytokines. The activation requires the translocation of CD244 on the same cell [28] suggesting that the stimulation occurs via CD244, which, unlike CD48, can signal via intracellular kinases [29]. There is further indication that the manner of anchoring of CD48 on NK cells differs from that on B cells.…”
Section: Evidence For Nk-cell Regulation Of B-cell Responsesmentioning
confidence: 92%
See 1 more Smart Citation
“…Surprisingly, however, anti-CD48 immobilized on plastic, can stimulate NK cells to augment their production of cytokines. The activation requires the translocation of CD244 on the same cell [28] suggesting that the stimulation occurs via CD244, which, unlike CD48, can signal via intracellular kinases [29]. There is further indication that the manner of anchoring of CD48 on NK cells differs from that on B cells.…”
Section: Evidence For Nk-cell Regulation Of B-cell Responsesmentioning
confidence: 92%
“…These dramatically opposing functions may be attributed to different splice forms of the transcript that result in alternative intracellular signal transduction [57]. However, the presence of the ligand, CD48, for the receptor, on the same cell may also affect its function depending on the extent of intra vs. intercellular crosslinking that may be modulated by interaction with other cell types that express CD48 [28,[58][59][60]. It is interesting that the cell surface molecule, CD48 is also encoded within the Sle1b locus and a number of reports have indicated NK cell-interactions between CD244 and CD48 expressed on other NK cells as well as on other cell types that may be manifested in functional sequalae [61][62][63].…”
Section: The Role Of Nk Cells In the Production Of Anti-nuclear-antibmentioning
confidence: 96%
“…Our previous findings showed that ligation by anti-CD48 can induce the transcription of IL-13 mRNA in IL-2-propagated NK cells and that this stimulation is correlated with a relocation of one of the two ligands for CD48 and CD244, on the same cell [6]. In order to determine if anti-CD48 can stimulate NK cells in vivo, PBLs were isolated on consecutive days after injection of the antibody into B6 mice.…”
Section: Resultsmentioning
confidence: 99%
“…Crosslinking of CD48 on NK cells leads to aggregation of CD244 on the same cell, resulting in phosphorylation of tyrosine residues and subsequent activation of -cytokine production [6]. In vitro experiments utilizing interleukin (IL)-2-propagated NK cells have indicated that stimulation of B cells by NK cells requires the presence of CD48 on B cells and leads to interferon (IFN)-γ-independent activation of downstream exons of the immunoglobulin (Ig) locus as revealed by germline transcriptions [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…2B4/CD48 interactions in NK cells are required for the enhanced proliferation and the development of optimal cytolytic and secretory NK effector functions during IL-2 activation [54]. Increased expression of CD48 on the NK cells may allow this ligand to be presented to the 2B4 receptor on opposing NK, T or B cells, thereby priming the NK cells to express IL-13 in the presence of another co-stimulatory signal [55].Human CD97 is a member of the EGF-TM7 family of adhesion class heptahelical receptors and was identified as an early activation marker for human lymphocytes [56]. We observed and validated increased CD97 level in response to IL-2 by real time RT-PCR (Fig.…”
mentioning
confidence: 99%